Label-free proteomic analysis to characterize ginger from China and Ghana. (30th May 2018) - Yin, Xiaojian; Wang, Shi-Lei; Alolga, Raphael N.; Mais, Enos; Li, Ping; Yang, Pingfang; Komatsu, Setsuko; Qi, Lian-Wen
Highlights: Ginger rhizomes of two geographical origins were distinguished. 14 metabolites were identified as the differential markers for the discrimination. 100 and 80 proteins were identified to be responsible for the ginger difference. Proteomic data is complementary with metabolomic data. Abstract: Ginger is a popular spice used in food and beverages. In this study, we sought to characterize and differentiate ginger samples of Ghana and China origin using label-free proteomic and untargeted metabolomic analyses. As result, a total of 180 proteins significantly changed between the ginger samples from both studied countries. Among them, 17 proteins were specifically identified in the Chinese ginger, while 23 proteins were only identified in the Ghanaian ginger. Function and bioinformatics analyses indicated that changes in carbon metabolism, secondary metabolites biosyntheses, citrate acid cycle, and amino acids biosyntheses-related pathways contributed to the differences. These results were confirmed through the identification of 14 significantly changed metabolites including diarylheptanoids and gingerols. Importantly, change tendencies of these metabolites corresponded to changes in abundance of the protein enzymes involved in their syntheses. These results suggest that changes in metabolism-related protein enzymes are responsible for the intraspecies difference of the ginger samples.